Pemanfaatan Kompos Kulit Durian untuk Mengurangi Dosis Pupuk N Anorganik pada Produksi Tanaman Sawi Hijau (Brassica junceae) - FAUZI, AHMAD RIFQI; PUSPITAWATI, MUTIARA DEWI (Agrotrop : Journal on Agriculture Science; Vol 7 No 1 (2017)DO - 10.24843/AJoAS.2017.v07.i01.p03, 2017)
Utilization Compost of Durian Shell to Reduce Dose of N Inorganic Fertilizer in Green Cabbage (Brassica junceae) Production. The high public demand for organic products are not comparable with the level of production. One of alternative producing agricultural healthy products is using agricultural waste as organic fertilizer for crop production. Durian shell can be used as an alternative material to make organic fertilizer. The study said that the durian shell can be used into useful organic fertilizer for plants and improving soil chemical properties. Based on this potential, research on the use of organic fertilizer from shell of durian need to performed. The results indicate that the solid organic fertilizer durian shell contains 14.6% C- organic, 1.69% N, 0.16% P2O5, and 1:20% K2O. The research aims to determine the effect of organic fertilizer from shell of durian and test their effectiveness in reducing the dose of inorganic N fertilizer on growth and yield of green cabbage (Brassica junceae). This research was conducted with randomized complete block design at the Experimental Garden Trilogy University, Jakarta. Research in the field include the dosage of organic fertilizer (0, 10, and 20 t / ha) and inorganic N fertilizer (0%, 50%, 75% and 100% of the dose recommendation of 250 kg / ha). The results showed no differences plant growth in all treatments. Fresh wet of shoot in the treatment of 20 tons of organic fertilizer + 50% inorganic fertilizer dose did not differ significantly by treatment with 20 tons of inorganic fertilizer + 100% inorganic fertilizers. This result conclused the application of organic fertilizer durian shell is able to reduce the dosage of inorganic fertilizer up to 50%.